Human Resources Transformation in the Digital Era: Success Strategies for the Future - Dirwan; Rajindra (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
Transforming Human Resources (HR) in the digital era has become the main focus for companies and organizations in adapting to rapid changes in technology and the business environment. In this context, this article explains the success strategies needed to face future challenges in HR management. The importance of HR transformation in the digital era cannot be denied, considering that digital technology has changed how companies operate, communicate, and compete. Quality human resources, technology skills, and adapting to change are precious assets. This article will discuss several critical strategies for successfully managing HR in the digital era, including developing digital competencies, increasing collaboration between departments, and using data analytics for more intelligent decision-making. Additionally, this article will highlight the role of effective leadership in guiding HR transformation. Leaders who understand the challenges and opportunities of the digital era and can inspire and motivate teams are the key to success in implementing change. In conclusion, HR transformation in the digital era is a critical step for companies and organizations that want to remain relevant and competitive. By following the success strategies discussed in this article, companies can prepare for a future filled with technological change and a dynamic business environment. HR transformation is not an option but rather a necessity to achieve long-term success.